2020
DOI: 10.2147/cmar.s239264
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of the Body Mass Index on Hemorrhage After Surgery for Thyroid Cancer</p>

Abstract: Objective: To investigate the effects of different values of the body mass index (BMI) on postoperative hemorrhage (PH) in thyroid cancer (TC) and its clinical management. Methods: This retrospective cohort study selected 43 patients with hemorrhage after TC surgery in 7413 cases. Patients were divided based on the BMI (kg/m 2) into normal (24), overweight group (24 ≤BMl<28) and obese (≥28) groups. Clinical and pathologic data, bleeding cause, bleeding site, treatment and prognosis were assessed. Results: BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…There were 38 studies 43,45,46,59‐91,211,212 (40 cohorts; 2,361,275 participants) of cancer populations (Table S3); 17 cohorts were in East Asia, 10 cohorts in North America, 7 in Europe, 2 were international cohorts, 2 were in West Asia, and 1 each in South America and Africa. Mean age of participants ranged from 17 to 75 years.…”
Section: Resultsmentioning
confidence: 99%
“…There were 38 studies 43,45,46,59‐91,211,212 (40 cohorts; 2,361,275 participants) of cancer populations (Table S3); 17 cohorts were in East Asia, 10 cohorts in North America, 7 in Europe, 2 were international cohorts, 2 were in West Asia, and 1 each in South America and Africa. Mean age of participants ranged from 17 to 75 years.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] An increasing number of studies have found that obesity is not only a risk factor for metabolic syndrome, diabetes, cardiovascular and cerebrovascular diseases, but also a variety of malignant tumors. 7,8 The International Agency for Research on Cancer has indicated that obesity is a risk factor for gastric cancer, colorectal cancer, liver cancer, pancreatic cancer, postmenopausal breast cancer, and other malignant tumors, and that BMI also has a significant dose-response relationship with cancer risk. 9 Global population data for 2012 show that countries with a high incidence of overweight and obesity have a significantly increased number of patients with new malignant tumors comparison with BMI health groups.…”
Section: Introductionmentioning
confidence: 99%
“…Early postoperative bleeding is associated with hemostasis failure or coagulation defects [ 19 ]. Taking NSAIDS and hypertension together is a common cause of postoperative bleeding [ 36 , 37 ]. In our opinion, preoperative coagulopathy should be given particular attention, and blood pressure should be maintained normal in individuals.…”
Section: Discussionmentioning
confidence: 99%